Holes in the Dike: The Global Savings Glut, U.S. House Prices, and the Long Shadow of Banking Deregulation. Issue 4 (24th September 2019) - Hoffmann, Mathias; Stewen, Iryna
Abstract: We show how capital inflows into and financial deregulation within the United States interacted in driving the recent boom and bust in U.S. housing prices. Interstate banking deregulation during the 1980s cast a long shadow: in states that opened their banking markets to out-of-state banks earlier, house prices were more sensitive to aggregate U.S. capital inflows during 1997–2012. Capital inflows relaxed the value-at-risk constraints of geographically diversified ("integrated") U.S. banks more than those of local banks. Therefore, integrated banks absorbed a larger share of capital inflows and expanded mortgage lending more. This drove up housing prices.